Stewart Postharvest Review - Singh, Zora; Khan, Ahmad (Postharvest solution Uk Ltd, 2010)
Purpose of review: Plum fruit exhibit varying types of ripening behaviour that is highly dependent on genotype, harvest maturity, andpre- or postharvest handling practices. This article focuses on recent advances in the physiology of plum fruit ripening.Findings: Recent studies have reported that in plums: (1) harvest maturity is associated with the ability of fruit to ripen properly, whichultimately affects consumer acceptance; (2) harvest maturity, storage temperature and storage period affect the level of sugars and organicacids; (3) malonyl 1-amino-cyclopropane-1-carboxylic acid and malonyl transferase activities are the main regulatory factorscontrolling fruit ripening and some other possible ethylene-related disorders during cold storage; (4) development of chilling injurysymptoms after cold storage are associated with ethylene biosynthesis and abnormalities of cell wall metabolism including reduction inpectin solubilisation and depolymerisation and decrease of galactose-rich pectin as well as postharvest oxidative stress; (5) great variationsexist in the concentrations of bioactive compounds and antioxidant activities depending on various pre- and postharvest factors.Directions for future research: Highly perishable nature, delicate skin, chilling sensitivity, and other postharvest physiological disorders,and the consistent supply of high quality fresh and safe fruit to the consumer are great challenges to postharvest physiologists.Development of non-destructive maturity assessment, quality evaluation methods for plum fruit warrants investigation. Molecular andconventional breeding approaches to regulating plum fruit ripening and improving their shelf-life have not resulted in substantial success.Determining whether ethylene is directly involved in promoting pigment accumulation or is triggered by another effector needsfurther investigation. Various factors that may affect the development of postharvest oxidative stress such as fruit ripening and storagedisorders in plums (including genotype, harvest maturity, storage temperature, storage period and atmosphere composition) warrantfurther investigation.